2020
DOI: 10.3389/fpls.2020.01300
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Characterization of Single-, Double- and Triple-Viral Diseases of Wheat With a Hand-Held Raman Spectrometer

Abstract: Plant diseases can reduce crop yield by up to 100%. Therefore, timely and confirmatory diagnosis of plant diseases is strongly desired. Typical pathogen assaying methods include polymerase chain reaction (PCR) and enzyme-linked immunosorbent assay (ELISA). These approaches are quite useful but are also time-consuming and destructive to the sample. Raman spectroscopy (RS) is a modern analytical technique that enables non-invasive plant disease detection. In this study, we report on Ramanbased detection of wheat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Previous works have demonstrated that RS techniques provide a clear differentiation between biotic stress (bacterial infection), abiotic stress (nutritional deficiencies) and healthy plants [ 16 ]. RS has the sensitivity to differentiate a simple or multiple viral infection in the same host [ 18 , 62 ], including the presence of secondary infections [ 30 ]. Additional works are required to determine the Raman spectral specificities to the different diseases that affect tomato plant.…”
Section: Resultsmentioning
confidence: 99%
“…Previous works have demonstrated that RS techniques provide a clear differentiation between biotic stress (bacterial infection), abiotic stress (nutritional deficiencies) and healthy plants [ 16 ]. RS has the sensitivity to differentiate a simple or multiple viral infection in the same host [ 18 , 62 ], including the presence of secondary infections [ 30 ]. Additional works are required to determine the Raman spectral specificities to the different diseases that affect tomato plant.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Kurouski and group demonstrated that RS could be used for confirmatory identification of viruses in wheat (Farber et al, 2020a). Farber and co-workers found that RS can be used to differentiate between healthy wheat and wheat infected by wheat streak mosaic virus (WSMV) and barley yellow dwarf virus (BYDV).…”
Section: Raman-based Diagnostics Of Viral Diseasesmentioning
confidence: 99%
“…This high sensitivity to small changes in plant biochemistry also enables Raman-based identification of plant species and their varieties, as well as allows for Raman-based selection and breeding of plants (Krimmer et al, 2019;Farber et al, 2020b,c;Sanchez et al, 2020a,d). Although to date, most of the reported experiments were made in greenhouses (Altangerel et al, 2017;Mandrile et al, 2019;Sanchez et al, 2020b,c), there is a growing body of evidence about successful use of RS in the field (Sanchez et al, 2019bFarber et al, 2020a). Once this practice will become the routine of research studies -recognition of RS as a reliable agricultural method will tremendously increase.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…This eliminates the need for transportation of plant material, further reducing the cost of analysis, simultaneously minimizing the potential spread of pathogens. Experimental results reported by the our group [ 10 , 11 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] and other research laboratories [ 12 , 21 , 22 , 23 , 24 ] show that hand-held Raman spectrometers could be used for fast (one second spectral acquisition time) and nearly 100% accurate diagnostics of biotic and abiotic stresses [ 10 , 11 , 13 , 16 , 19 , 20 , 25 ]. This innovative sensing approach is based on detecting and identifying pathogen-induced changes in plant biochemistry.…”
Section: Introductionmentioning
confidence: 99%